On the Error Estimate of Linear Finite Element Approximation to the Elastic Contact Problem with Curved Contact Boundary (Journal of Computational Mathematics, 2021)
In this paper, the linear finite element approximation to the elastic contact problem with curved contact boundary is considered. The error bound $O(h^{1/2})$ is obtained with requirements of two times continuously differentiable for contact boundary and the usual regular triangulation, while I.Hlavacek et. al. obtained the error bound $O(h^{3/4})$ with requirements of three times continuously differentiable for contact boundary and extra regularities of triangulation (c.f. [2]).